2022
DOI: 10.1136/bmjopen-2021-055679
|View full text |Cite
|
Sign up to set email alerts
|

Virtual visiting in intensive care during the COVID-19 pandemic: a qualitative descriptive study with ICU clinicians and non-ICU family team liaison members

Abstract: ObjectiveTo understand the experiences and perceived benefits of virtual visiting from the perspectives of intensive care unit (ICU)-experienced clinicians and non-ICU-experienced family liaison team members.DesignQualitative descriptive study.SettingAdult intensive care setting across 14 hospitals within the UK National Health Service.ParticipantsICU-experienced clinicians and non-ICU-experienced family liaison team members deployed during the first wave of the COVID-19 pandemic.MethodsSemistructured telephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The results of our study align well with the mental health impact reported in published studies of patient and family experience of visiting restrictions in adult (4,5,26) and pediatric intensive care unit settings (27)(28)(29). Rose et al (5) reported a large multicenter cohort representing adult family members experiencing at least one ICU virtual visit in 37 UK hospitals in the second COVID-19 wave and found high levels of psychological distress with over 60% reporting severe distress prior to their first virtual visit with their loved one.…”
Section: " [P14]supporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study align well with the mental health impact reported in published studies of patient and family experience of visiting restrictions in adult (4,5,26) and pediatric intensive care unit settings (27)(28)(29). Rose et al (5) reported a large multicenter cohort representing adult family members experiencing at least one ICU virtual visit in 37 UK hospitals in the second COVID-19 wave and found high levels of psychological distress with over 60% reporting severe distress prior to their first virtual visit with their loved one.…”
Section: " [P14]supporting
confidence: 91%
“…During this time, several organizations looked to launch various versions of virtual visiting opportunities for families of admitted patients. The majority of the published literature on such programs to date has been focused on programs implemented in adult and pediatric intensive care units, where virtual visiting has been very successful in connecting patients, families, and health care providers in a timely way (4)(5)(6)(7)(8)(9). To our knowledge there is very little, if any, published on virtual family visiting programs in general medical wards or other areas in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving FCC for adult patients required innovation and dedicated resources to facilitate interventions such as virtual visits, family orientation and to mark the story of the patient’s illness journey. Virtual visits were seen as beneficial for communication and orientation activities and also provided an opportunity for family members to make sense of their own emotions and coping ( 7 ). Typically, facilitating FCC would fall to bedside nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual ICU visitation was shown to be beneficial for patients (reduced psychological distress), families (improved sense-making, happiness, gratitude), and the health care team (improved morale). [22][23][24] The use of virtual communication strategies with the health care team during the pandemic was also shown to be a positive experience for family members and health care providers alike. 25 Increasing virtual visitation and other virtual family engagement strategies, such as virtual participation in ICU rounds, can also be useful for family members who live far away from the hospital or who have work or social reasons that they cannot attend in-person, as well as for infection control reasons.…”
Section: Health Care System Barriers To Family Engagementmentioning
confidence: 99%